THE APPLICATION OF THE ANALYTICAL NETWORK PROCESS (ANP) METHOD TO DETERMINE THE DOMINANT FACTOR CAUSING THE ACCIDENT IN THE WEST SURABAYA SAILWAY - Santosa, Yoyok Nurkarya; Pamungkas, Taufik; Rakhman, Rofi Hidayatur (JOURNAL ASRO, 2023)
The Surabaya West Shipping Route is the second busiest shipping channel in Indonesia after the entry channel Tanjung Priok. Due to the long and narrow shipping lanes and the large flow of ships going in and out of ports, it is very vulnerable to maritime accidents, be it grounding, ship collisions, or other types of accidents, which of course will have a negative impact on Intersolar shipping. By looking at the facts mentioned above, it is deemed necessary to carry out scientific research so that we can determine the dominant factors that cause shipping accidents in the West Surabaya Shipping Channel so that later it is hoped that the main criteria that cause accidents will also be known. In making decisions about the causes of accidents in the Surabaya West Shipping Channel, existing problems cannot be arranged in a hierarchical form because they involve interactions and dependencies of higher-level elements on lower-level elements. Therefore, in this research, the Analytic Network Process (ANP) method is used which has the ability to accommodate the relationship between criteria or alternatives. Keywords: Analytic Network Process (ANP), Alternatives, West Surabaya Shipping Route, Main Criteria